Cognitive Development in the Golden Ages - Windisyah Putra (PT FORMOSA CENDEKIA GLOBAL, 2022)
When children develop their cognitive abilities, two processes occur within them, namely the first is the process of organizing information, namely the process of linking information received with existing knowledge structures, and the second is the process of adaptation, which contains two activities; (1) combining received knowledge (assimilation) and (2) changing the existing knowledge structure with a new knowledge structure (accommodation). This change results in a multi-faceted interaction network. Developmental factors are also influenced by the phase before birth (prenatal), at birth (perinatal) and after birth (postnatal). At least it can be concluded that every child is unique and no two children have exactly the same cognitive abilities, even though they were born in identical twins from one egg cell. Early childhood is in the most rapid phase of cognitive development. Cognitive development of children begins in the womb. It is influenced by many factors, including physical maturity, experiences and interactions between children and the people around them. Cognitive skills in children occur through an elaboration process in the brain (mind) not outside the brain a brief statement of the results and implications, if any.